VD_FINDINFO HC / 2011 / 150 vom 23. März 2011 - VD Tribunal cantonal (2011)
OBLIGATION D'ENTRETIEN, CONJOINT, MODIFICATIONEN GÉNÉRAL, MESURE PROVISIONNELLE | 163 CC, 176 al. 1 CC, 268 al. 1 CPC (CH), 310 CPC (CH)